Evolution of Magnetic Reconnection in an Electron-scale Current Sheet - Yundan Guan; Quanming Lu; San Lu; Rongsheng Wang (The Astrophysical Journal)
Recently, a new type of magnetic reconnection, electron-only reconnection—where there is no obvious ion flow and heating—has been observed in various plasma environments. Previous kinetic simulations have shown that electron-only reconnection is a precursor of standard reconnection. In this paper, by performing a 2.5-dimensional particle-in-cell simulation, we investigate the evolution of electron-only magnetic reconnection to standard magnetic reconnection in a current sheet, whose initial width is of the electron inertial length. In the electron-only reconnection stage, electron outflow produces the electron-scale ${B}_{z}$ pileup, and ions are slightly accelerated in the outflow direction by the Hall electric field force. As the reconnection electric field expands and ${B}_{z}$ is piled up to the ion scale, ions start to be further accelerated inside the ion diffusion region and reflected by the ${B}_{z}$ to the outflow direction. With ${B}_{z}$ pileup as the bond, ions gradually transit from being accelerated by the Hall electric field to being coupled in reconnection by the Lorentz force.